Development of a single-run liquid chromatography-mass spectrometry analysis for the detection of 11 multiclass contaminants of emerging concern using a direct filtration method - Razak, Muhammad Raznisyafiq; Aris, Ahmad Zaharin; Sukatis, Fahren Fazzer; Mohd Zaki, Muhammad Rozaimi; Zainuddin, Azim Haziq; Mohamad Haron, Didi Erwandi; Md Yusoff, Fatimah; Yusof, Zetty Norhana Balia (Wiley, 2022)
In toxicological analysis, the analytical validation method is important to assess the exact risk of contaminants of emerging concern in the environment. Syringe filters are mainly used to remove impurities from sample solutions. However, the loss of analyte to the syringe filter could be considerable, causing an underestimate of the analyte concentrations. The current study develops and validates simultaneous liquid chromatography-mass spectrometry analysis using a direct filtration method to detect four groups of contaminants of emerging concern. The adsorption of the analyte onto three different matrices and six types of syringe filters is reported. The lowest adsorption of analytes was observed in methanol (16.72%), followed by deionized water (48.19%) and filtered surface lake water (48.94%). Irrespective of the type of the matrices, the lowest average adsorption by the syringe filter was observed in the 0.45 μm polypropylene membrane (15.15%), followed by the 0.20 μm polypropylene membrane (16.10%), the 0.20 μm regenerated cellulose (16.15%), the 0.20 μm polytetrafluoroethylene membrane (47.38%), the 0.45 μm nylon membrane (64.87%) and the 0.20 μm nylon membrane (71.30%). In conclusion, the recommended syringe filter membranes for contaminants of emerging concern analysis are polypropylene membranes and regenerated cellulose, regardless of the matrix used.